Added Value of Genomic Surveillance of Virulence Factors in Shiga Toxin-Producing Escherichia coli in New South Wales, Australia - Sim, Eby M.; Kim, Ryan; Gall, Mailie; Arnott, Alicia; Howard, Peter; Valcanis, Mary; Howden, Benjamin P.; Sintchenko, Vitali (Frontiers in Microbiology, 2021)
The disease caused by Shiga toxin-producing Escherichia coli (STEC) remains a significant public health challenge globally but the incidence of human STEC infections in Australia remains relatively low. This study examined the virulence characteristics and diversity of STEC isolates in the state of New South Wales between December 2017 and May 2020. Utilisation of both whole and core genome Multi Locus Sequence Typing (MLST) allowed for the inference of genomic diversity and detection of isolates that were likely to be epidemiologically linked. The most common STEC serotype and stx subtype detected in this study were O157:H7 and stx1a, respectively. A genomic scan of other virulence factors present in STEC suggested interplay between iron uptake system and virulence factors that mediate either iron release or countermeasures against host defence that could result in a reduction of stx1a expression. This reduced expression of the dominant stx genotype could contribute to the reduced incidence of STEC related illness in Australia. Genomic surveillance of STEC becomes an important part of public health response and ongoing interrogation of virulence factors in STEC offers additional insights for the public health risk assessment